Treatment of acute cannabinoid overdose with naloxone infusion. Issue 1 (1st January 2017) - Richards, John R.; Schandera, Verena; Elder, Joshua W.
ABSTRACT: The legalization of cannabis has resulted in rising use, wider availability, and development of highly potent strains. Patients presenting to the emergency department with cannabis toxicity and cannabinoid hyperemesis syndrome are becoming more prevalent. We present a case of a middle-age male with heavy acute cannabis use resulting in hypoventilation, somnolence, and hypothermia successfully treated in the emergency department and medical intensive care unit with a continuous naloxone infusion. The overlapping endocannabinoid and endogenous opioid systems may explain this patient's response to therapy, and this synergistic relationship is discussed.